Security Enhancement of Route Optimization in Mobile IPv6 Networks - Zare Anari, Abbas Mehdizadeh (2008)
Mobile IPv6 is an IP-layer protocol that is designed to provide mobility support.It allows an IPv6 node to arbitrarily change its location in the IPv6 network while maintaining the existing connection by handling the change of addresses at the Internet layer. Route optimization is standard in Mobile IPv6 to eliminate inefficient triangle routing. Several methods were proposed to secure route optimization. Return routability was adopted by Internet Engineering Task Force (IETF) with its security protocol based on RFC 3775. Return routability is an infrastructureless, lightweight procedure that enables a Mobile IPv6 node to request another IPv6 node to check and test the ownership of its permanent address in both home network and current visited network. It authorizes a binding procedure by the use of cryptographically token exchange. However, return routability protocol in route optimization is to protect messages and is not able to detect or prevent an attacker which tampers against data. In this thesis, focus is given on Mobile IPv6 route optimization test-bed with enhanced security in terms of data integrity. The proposed method can be performed on top of the return routability procedure to detect and prevent Man-In-The-Middle attack by using encryption if any attack is detected. This also eliminates the additional delay compared to using encryption from the beginning of a connection. A real-time experimental test-bed has been set up, which is comprised of hardware, software and network analysis tools to monitor the packet flow and content of data packets. The test-bed consists of four computers acting as Mobile Node, Home Agent, Correspondent Node, and Router, respectively. To ensure the accuracy and integrity of the collected data, the Network Time Protocol (NTP) was used between the packet generator (Mobile Node) and packet receiver (Correspondent Node) to synchronize the time. The results show that the proposed method is able to work efficiently, maintaining 99% data security of route optimization in Mobile IPv6 (MIPv6) networks. The overall data integrity (by means of security) is improved 72% compared to existing MIPv6 by at a cost of 0.1 sec added overall delay, which is within the tolerable range by the network.